Differences in Tooth Development in Patients With Unilateral Cleft Lip and Palate - Marie Schwarting; Heinrich Wehrbein; Irene Schmidtmann; Christina Erbe; Susanne Wriedt (Clinical and Experimental Dental Research)
ABSTRACT Objectives The aim of this study was to investigate tooth development in patients with unilateral cleft lip and palate (UCLP) and unilateral cleft lip and alveolus (UCLA). Material and Methods A retrospective case–control study was carried out; 180 panoramic radiographs (OPGs) from non‐syndromic patients (160 UCLP, 20 UCLA) treated at the University Medical Center Mainz (2019–2022) were analyzed. Patients were matched to a control group by calendar age, gender, and ethnicity. Inclusion criteria were verified through clinical data, photographs, and radiographs. No follow‐up was conducted for this study. Results The cleft group showed a significantly lower dental age compared to the control group (10.72 ± 2.65 vs. 11.41 ± 2.79; p = 0.017), with a mean difference of 0.69 years (95% CI: 0.13–1.25 years). Tooth development was slower on the cleft side (p = 0.001), and maxillary teeth lagged behind mandibular teeth (p < 0.001). The difference in the control group was somewhat smaller, with a mean difference of 0.11 degrees of mineralization in the control group compared to 0.25 degrees of mineralization in the cleft group. In UCLP patients, significant mineralization differences were noted for the lateral incisors (p = 0.004), the central incisor (p = 0.047), and canine (p = 0.030). Conclusions Patients with unilateral clefts show delayed tooth development and dental age, particularly in the affected quadrant. In everyday treatment, attention should be paid to a later start of orthodontic tooth movement to avoid damaging the slower developing roots.